Новые схемы многопульсных выпрямителей - Волков, Игорь Владимирович; Каршенов, Дмитрий Петрович (НТУ "ХПИ", 2013)
Получены малоискажающие многопульсные несимметричные трехфазные выпрямительные системы, в которых уменьшение искажения синусоидальности входного тока обеспечивается оптимальным заданием угла между каналами фазосдвигающего узла без увеличения количества каналов (мостов).

It is gained a little distorting multi-pulse asymmetrical three-phase systems of rectifiers in which lowering of Total Harmonics Distortion (THD) of input current is provided with optimum value of the angle between the channels of phase-shifting knots without increase in quantity of channels (bridges)
New variants multi-pulse rectifiers
Keywords: коэффициент искажения синусоидальности; высшие гармоники; нелинейный элемент; nonlinear element; harmonics; multi-pulse rectifier